Gold nanoparticles as theranostic platform - Jha A.; Kumar M.; Mishra B. (My University, 2025)
The theranostic application of gold nanoparticles is a significant area of study, which includes attempts to mitigate the side effects and enhance the delivery and efficacy. Owing to unique physicochemical, optical, and electrical properties, gold nanoparticles have a high potential to be developed as a new-generation smart theranostic tool. Gold nanoparticles offer a new strategy for site-specific imaging and therapeutic function, concurrently in a single platform. Gold nanoparticles offer an enticing way to diagnose the early stages of the disease, monitor the in vivo fate of nanomedicines, assess the real-time release of loaded biomolecules, and treatment. This chapter focuses on various types of gold nanoparticles, their synthesis, and applications as a theranostic agent; therapeutics delivery, photothermal/photodynamic therapy, and bioimaging. © 2023 Elsevier Inc. All rights reserved.